Non-perturbative vacua for M-theory on G(2) manifolds - de Carlos, B; Lukas, A; Morris, S (2004)
We study moduli stabilization in the context of M-theory on compact manifolds with G2 holonomy, using superpotentials from flux and membrane instantons, and recent results for the Kähler potential of such models. The existence of minima with negative cosmological constant, stabilizing all moduli, is established. While most of these minima preserve supersymmetry, we also find examples with broken supersymmetry. Supersymmetric vacua with vanishing cosmological constant can also be obtained after a suitable tuning of parameters. © SISSA/ISAS 2005.